An Analysis of HOTS Level Questions on the Indonesian Objective Tests - Tia Anggraini Putri; Didi Yulistio; Agus Trianto (IJLECR (International Journal of Language Education and Cultural Review), 2023)
This study aimed to describe HOTS-level questions in the objective tests at the end-of-semester Indonesian exam for class XII at SMA Negeri 3 Bengkulu Tengah. The researcher's description was based on Anderson & Krathwohl's theory. This research was a qualitative descriptive study. The data source in this study was in the form of documents for the end-of-semester exams for class XII Indonesian at SMA Negeri 3 Bengkulu Tengah, totaling 105 questions using documentation data collection techniques. The analysis showed that HOTS questions still tend to be few and have not fully used HOTS-level questions. 11 questions meet the characteristics of HOTS questions or the equivalent of 10% of the data used. 10% of HOTS questions were dominated by the C4 thinking process dimension (analyzing), which consists of 6 questions (6%), the C5 thinking process dimension (evaluating) 4%, and the C6 thinking process dimension (creating) 1%. For the knowledge dimension, the HOTS questions were dominated by questions that measure the conceptual knowledge dimension.